Location choice and employment decisions: a comparison of German and Swedish multinationals - Sascha O. Becker; Karolina Ekholm; Robert Jäckle; Marc-Andreas Mündler (Deutsche Bundesbank, 2005)
Using data for German and Swedish multinational enterprises (MNEs), this paper assesses international employment patterns. It analyzes determinants of location choice and the degree of substitutability of labor across locations. Countries with highly skilled labor forces attract German MNEs, but we nd no such evidence for Swedish MNEs. This is consistent with the hypothesis that German MNEs locate production stages intensive in high-skilled labor abroad. In MNEs from either country, af liate employment tends to substitute for employment at the parent rm. At the margin, substitutability is the strongest with respect to af liate employment in Western Europe. A one percent larger wage gap between Germany and locations in Central and Eastern Europe (CEE) is estimated to be associated with 900 fewer jobs in German parents and 5,000 more jobs in af liates located in CEE. A one percent larger wage gap between Sweden and CEE is estimated to be associated with 140 fewer jobs in Swedish parents and 260 more jobs in af liates located in CEE.
Keywords: J21; F23; J23; F21; 330; Multinational enterprises; location choice; multinomial choice; labor demand; translog cost function; Multinationales Unternehmen; Standortwahl; Arbeitsnachfrage; Arbeitskosten; Vergleich; Schweden; Deutschland